Analysis of Liquidity, Firm Size, Profitability, Capital Structure and Firm Value of Oil and Gas Companies on the IDX - M. Roni Riswandi; Solikah Nurwati; Sanjayanto Nugroho (Jurnal Manajemen Sains dan Organisasi, 2023)
Purpose - The Effect of Liquidity, Firm Size, and Profitability on Firm Value withCapital Structure as an intervening variable in Oil and Gas Companies on theIndonesia Stock Exchange Design/Methodology/Approach – The research method used in this study is aquantitative research approach. The analysis unit of this study is oil and gascompanies listed on the Indonesia Stock Exchange in 2017-2020, totaling 9companies with purposive sampling techniques. The collected data was analyzedusing the Partial Least Square (PLS) approach, the software used was SmartPLS3.3.Findings – The results showed that, liquidity has a positive but not significant effecton the value of the firm, the size of the firm has a negative but insignificant effect onthe value of the firm, profitability has a negative but not significant effect on thevalue of the firm, liquidity has a positive but not significant effect on the capitalstructure, the size of the firm has a positive but insignificant effect on the capitalstructure, profitability has a positive and significant effect on the capital structure,the capital structure has a positive and significant effect on the value of the firm, thecapital structure is unable to mediate the effect of liquidity on the value of the firm,the capital structure is unable to mediate the influence of the size of the firm on thevalue of the firm, the capital structure is able to mediate the influence of profitabilityon the value of the firm. For subsequent researchers, it is recommended to usedifferent independent variables, it is also advisable to conduct research oncompanies with more diverse characteristics. Thus, the results obtained can berepresentative to be drawn conclusions by comparing each sector of companieslisted on the Indonesia Stock Exchange..